EFFECTIVENESS OF CAKE APPLICATION ON STUDENT'S VOCABULARY MASTERY - Nikmah, Zulva Minla Dunka (Journal of English Teaching and Linguistics Studies (JET Li), 2023)
This study aims to determine the effectiveness of using the Cake application for students' English vocabulary learning. This research is a quantitative research which is a pre-experimental study with a one-group pre-test post-test design. The population of this studywere students of the Bhinneka PGRI University English Education study program in the 2022/2023 academic year. The sample of this study were 8th semester students, totaling 19 students. The sample used by the researcher is a purposive sampling type. The instruments used were pretest and posttest. In the pretest, students are asked to do a test about English vocabulary before using the cake application. In the posttest, students were also asked to work on test questions after using the cake application. The results showed that the use of the cake application affected students' English vocabulary mastery. This can be seen from the results of data analysis that has been carried out from the pretest average value of 72.37, as a comparison to the posttest value of 83.42. In addition, it is also proven again by using hypothesis testing paired sample t-test. The result obtained is 0.003. In the paired t-sample test rules, if the significance is less than 0.05, then H0 is rejected and Ha is accepted. Based on the results of the study, it can be concluded that the use of the cake application affects students' English vocabulary learning